Penerapan Model Pembelajaran Kooperatif Tipe Make A Match Dalam Meningkatkan Aktivitas Belajar Matematika Materi Pecahan Sederhana Pada Siswa Kelas III SD Negeri Banjarsari 1 Tahun Ajaran 2022/2023 - ., Utami Tri Andriani; ., Nurul Saila; ., Ribut Prastiwi Sriwijayanti (CV. ITTC INDONESIA, 2023)
The application of the make-a-match cooperative learning model can increase learning activities. This research was motivated by the application of the make-a-match type of cooperative learning model in class III of SD Negeri Banjarsari 1 which could increase mathematics learning activities, so researchers were interested in researching the application of make-a-match type cooperative learning models in increasing learning activities. The problems in this study are how they make a match type of cooperative learning model improve learning activities, what are the constraints of applying the make-a-match type cooperative learning model in increasing learning activities, and what are the efforts or solutions in dealing with obstacles in applying the make a match type cooperative learning model in improve learning activities. In data collection procedures using data collection methods with observation, interviews, and documentation. The results of the study, the application of the make-a-match type of cooperative learning model can increase the mathematics learning activities of class III students of SD Negeri Banjarsari 1.